Effects of Different Flame-Retardant Treatments on the Sound Absorption Properties of Low-Density Fiberboard - Min Lee; Eun-Chang Kang; Sang-Min Lee (BioResources, 2023)
Internal finishing materials for large auditoriums or public facilities are regulated in South Korea to ensure their flame-retardant performance. Flame-retardant treatment of low-density fiberboard (LDF), an eco-friendly material, was performed to expand its use as a sound absorber by improving its fire safety. In this study, an LDF with a target density of 0.15 g/cm3 was prepared from radiata pine wood fibers and melamine–urea–formaldehyde resin, and recommended amounts of commercially available flame retardants (liquid type) were applied immediately after hot pressing. A powder-type flame retardant was blended with the resin used in LDF manufacture. The surface color and material changed partially depending on the flame-retardant type. The external application method slightly increased the moisture content and density, but it did not affect the physical properties of the LDF. The flame-retardant treatment reduced the emission of formaldehyde, as a scavenger. After treatment, the char area and char length of the LDFs decreased significantly to 9.42–23.64%, and 6.11–11.91%, respectively. The sound absorption performance of the flame-retardant-treated LDFs improved 4.08–9.11%, while their thermal-insulation performance remained unaffected. The flame-retardant-treated LDFs satisfy the regulation of flame retardancy, while maintaining sound absorption and thermal insulation functions.